The Effects of Land Ownership on Production, Labor Allocation, and Rice Farming Efficiency - Rondhi, Mohammad; Adi, Ad Hariyanto (Program Studi Agribisnis Fakultas Pertanian Universitas Muhammadiyah Yogyakarta, 2018)
Land is the main input in agricultural production and also a wealth-generating asset for farmers. There are three common forms of agricultural land ownership:owned land, rented land, and sharecropped (kedokan) land, where each of them are directly affects the farming performance. The purpose of this study was to analyze the effect of land ownerships on farm production, labor use, and farm economic efficiency. The sample used in this study were 150 farmers equally distributed in each ownership group from a population of 1039 farmers. Cobb-Douglas production function, F-test, and RC ratio were used to estimate production function, the difference in labor use, and farm economic efficiency. The results showed that rented land has the highest productivity followed by owned and sharecropped(kedokan) land. Meanwhile, the sharecroppedkedokan)land has the lowest labor use, followed by rented and owned land. However, in term of profitability, owned land is the highest followed by rented and sharecropped land. The results also showed that sharecropping(ngedok) as an informal contract farming between farmer and landlord was the best economic choice for the landlord. Furthermore, to improve farmers welfare, the landless farmers should be facilitated to own their own land.